CULTIVATING STUDENTS’ CRITICAL THINKING IN READING BY USING BOOK REPORT (CLOTHES HANGER) LESSON STUDY BASED ON SMAN 2 PEUSANGAN - SUSILAWATI; Misnar (Journal of English Education and Social Science, 2021)
The research of cultivating students’ critical thinking in reading by using book report (clothes hanger) lesson study based on SMAN 2 Peusangan has been done at SMAN 2 Peusangan. It was begun from July 15 2020 until July 25 2020. The problems of this research are; how does the use of book report (clothes hanger) as media cultivate students’ reading skill? And how do students’ responses toward the implementation of book report (clothes hanger) to the 11th grade students of SMAN 2 Peusangan?. Based on the research problems, there are two purposes of the research, namely; to know the use of book report (clothes hanger) as media to cultivate the students’ reading skill and to find out students’ responses toward the implementation of book report clothes hanger) to the 11th grade students of SMAN 2 Peusangan. The scope of this research focus on improving the students’ ability on reading Analytical Exposition Text by using book report (clothes hanger). This research is designed as lesson study-based research with three steps of research procedure, namely: planning the action, implementing and observing the action, and reflecting the action. The results of the research using the book report (clothes hanger) method based on lesson study showed that the class average score increased to 83.57, from the initial data (pre-test) 60.71. The percentage of completeness increased to 100% from the initial data which was only 50%. The analysis of the increase in students’ learning activeness was obtained through the results of observing students’ activity during the learning process that collected from the observation sheet which results showed a significant increase in student activeness. Based on the research results, it can be concluded that the implementation of lesson study-based book reports (clothes hanger) can improve the quality of students' reading learning, especially in the analytical exposition text of 11th grade SMAN 2 Peusangan.